Land use options in dry tropical woodland ecosystems in Zimbabwe: Introduction, overview and synthesis - Campbell, Bruce M.; Costanza, R.; Belt, M. van den (2000)
This article focuses on the ecological and economic interactions of woodland use in Western Zimbabwe. One of the aims was to investigate the use of modelling to achieve integration among disciplines. The integrated model draws on the models in the different papers in this issue of the journal. The model has five ecological sectors: all five sectors cover woodland use by local people and the state forestry organisation, two sectors agriculture, one sector population growth and land use, one sector carbon sequestration, and one sector to calculate net present values of the various uses. The state has usually attempted to keep people and their livestock out of the forest. It is shown that private benefits of cropland may be greater than those related to state or local use of the woodland, but further work is required to incorporate the public costs of subsidies to cropland, and the public benefits of woodland services. Livestock production in the woodlands is compatible with woodland management, both from economic and ecological perspectives. Expulsion of forest dwellers from the state forest makes little ecological impact on the woodland, and does not improve the economic value of the woodland to the state. However, if the Forestry Commission relaxes the current control on in-migration, it is likely that the woodland be rapidly depleted in the face of massive in-migration. Modelling is seen as a framework for integration of ecological and economic issues, but further work is required to incorporate institutional perspectives from the sociological and anthropological disciplines.